Problems and Prospects of Development of the Oil Exchange Market in the Russian Federation - Vasiljeva, Marina V.; Ponkratov, Vadim V.; Kharlamova, Elena Y.; Kuznetsov, Nikolay V.; Maramygin, Maksim S.; Volkova, Maria V. (International Journal of Energy Economics and Policy, 2019)
In the context of speculatively priced Russian oil on the world energy market, the oil exchange market development in the Russian Federation is updated. The purpose of the article was to rationalize conditions ensuring the crude oil market pricing by means of exchange trade development. The main objective of the scientific search was to justify state oil purchase as the main factor in improving the Russian oil exchange market liquidity at the present stage of its development. An optimal level of the ratio of public expenditures for oil exchange purchase to Russia’s GDP was determined. The optimal amount of public expenditures for oil exchange purchase for the second quarter of 2018 amounted to 2,384.64 billion rubles. The optimal amount of public expenditures for oil exchange purchase is 89.9 million tons per quarter. State procurement of such oil volumes as of today could ensure an increase in the oil exchange market liquidity. The research results may lay the groundwork for enhancing the state strategy efficiency to improve the pricing of Russia’s energy resources. Some practical focus areas substantiated in the article would contribute to the exchange market development at the present stage as a factor in the formation of an actual market price for Russian oil. Keywords: Oil Market, Oil Exchange Market, Participants in Oil Exchange Trade, Oligopolistic Oil Market, Russian Oil Industry JEL Classifications: G23; L52; O24 DOI: https://doi.org/10.32479/ijeep.7378